Khewra Trap: An Unusual Ultrapotassic Rock in the Salt Range of Pakistan - Jan, M. Q.; Faruqi, S. H. (Journal of Nepal Geological Society, 1995)
The classical stratigraphic sequence of the Salt Range contains thin flows of an ultrapotassic rock at its base. Commonly known as Khewra trap, it occurs at the top of the very late Proterozoic to Early Cambrian rocks consisting of marly anhydrite/gypsum, and oil shales overlying evaporites. The trap is an unusual rock consisting of euhedral to skeletal, spinifex, stellate phenocrysts in a very fine-grained to cryptocrystalline, locally glassy, matrix. The phenocrysts (up to 3 cm long) are considered to be Mg-rich enstatite now completely pseudomorphed by a mineral aggregate principally made up of talc with subordinate amounts of Mg-rich clays and, locally, quartz. The matrix is unaltered and almost entirely made up of Na-Ca-poor and Mg-Fe-rich K-Feldspar (sanidine-orthoclase), with granules, specks and dendroids of Fe-Oxide. Talc, Mg-rich clays, quartz, dolomite, and Fe-oxide constitute the amygdules. Chemical analyses of the rock samples from the trap are remarkably similar in composition except for some variation in iron oxide due, probably, to leaching during alteration. The rocks consist approximately of 60 wt% SiO2, 0.7% TiO2, 11% Al2O3, 2-5% Fe2O3, (total), 0.02% MnO, 10% MgO, 0.4% CaO, 0.5% Na2O, 9% K1O, and 0.04% P2O5. Normatively the rocks are essentially made up of orthoclase and orthopyroxene. The volcanism may be related to Late Proterozoic-Early Paleozoic rifting which also resulted in deposition of the evaporites, however, the major element chemistry casts doubts on such an interpretation. Detailed trace- and rare earth element geochemistry is in progress to throw light on the petrogenesis of these highly unusual rocks.